2016
DOI: 10.1080/14737159.2016.1217157
|View full text |Cite
|
Sign up to set email alerts
|

Management of high-risk HPV-positive women for detection of cervical (pre)cancer

Abstract: Introduction: Primary HPV-testing has been shown to provide a superior detection of women at risk of cervical (pre)cancer compared to cytology-based screening. However, as most high-risk HPV infections are harmless, additional triage testing of HPV-positive women is necessary to identify those with cervical (pre)cancer. In this paper, we compare the performance, advantages and limitations of clinically relevant available triage strategies for HPV-positive women. Areas covered: Many different colposcopy triage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 125 publications
(247 reference statements)
0
52
0
3
Order By: Relevance
“…The genes evaluated in this study may well serve as objective molecular tools to improve cervical cancer screening, especially as triage test after primary hrHPV testing [1,7,44]. In several countries, including The Netherlands, hrHPV testing is replacing cytology as primary screening method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genes evaluated in this study may well serve as objective molecular tools to improve cervical cancer screening, especially as triage test after primary hrHPV testing [1,7,44]. In several countries, including The Netherlands, hrHPV testing is replacing cytology as primary screening method.…”
Section: Discussionmentioning
confidence: 99%
“…Increased DNA methylation levels of several (candidate) tumor suppressor genes are associated with cervical cancer and a subset of its high-grade precursor lesions, i.e., cervical intraepithelial neoplasia grade 2 and 3 (CIN2 and CIN3) [1,6,7]. Using both targeted and genome-wide approaches, we previously identified 12 genes, including ANKRD18CP, C13orf18, EPB41L3 , and JAM3 [8,9]; SOX1 and ZSCAN1 [9,10]; GHSR, SST , and ZIC1 [11]; and FAM19A4, PHACTR3 , and PRDM14 [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical cancer development after a persistent infection with high‐risk HPV is driven by additional host cell changes such as altered DNA methylation 12, 17, 20, 21. In earlier work, we have shown that methylation assays targeting FAM19A4 and/or mir124‐2 genes have competitive performance against other triage options 22, 23, 24, 25, 26. In cross‐sectional and short‐term clinical follow‐up studies among both cervical screening and gynecologic outpatient populations, FAM19A4 methylation analysis has shown a similar sensitivity for cervical intraepithelial neoplasia lesions or worse (CIN3+) as compared to cytology 22, 24.…”
Section: Introductionmentioning
confidence: 96%
“…More than 180 types of HPV have been identified so far, and each type has evolved to infect and propagate in specific epithelial targets, such as the sole of the foot, non-genital skin, anogenital skin, anogenital mucosa and oropharyngeal mucosa2. Most HPV infections are subclinical and are typically cleared or suppressed by cell-mediated immunity within 1–2 years of exposure.…”
mentioning
confidence: 99%